1997
DOI: 10.1073/pnas.94.14.7412
|View full text |Cite
|
Sign up to set email alerts
|

Silent chromatin determines target preference of the Saccharomyces retrotransposon Ty5

Abstract: The HML and HMR mating loci of Saccharomyces cerevisiae are bound in silent chromatin, which is assembled at the f lanking E and I transcriptional silencers. The retrotransposon Ty5 preferentially integrates into regions of silent chromatin, and Ty5 insertions near the HMR-E silencer account for Ϸ2% of total transposition events. Most Ty5 insertions occur within 800 bp on either side of the autonomously replicating consensus sequence within HMR-E. Ty5 target preference is determined by silent chromatin, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 34 publications
(41 reference statements)
2
71
0
Order By: Relevance
“…59), but the cellular and viral factors that control the reaction and the site(s) of integration remain elusive (60). The integration process is better understood at the molecular level for retrotransposons Ty1, Ty2, Ty3, and Ty4, which have been shown to specifically integrate upstream to genes that are transcribed by RNA polymerase III (61-63), and for Ty5, which integrates into regions of silent chromatin via yeast proteins Sir (64,65). Like Sir proteins in yeast, the products of Pc-G genes in upper eukaryotes are involved in the maintenance of the silent state of chromatin, possibly by recruitment of histone deacetylase enzymes (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…59), but the cellular and viral factors that control the reaction and the site(s) of integration remain elusive (60). The integration process is better understood at the molecular level for retrotransposons Ty1, Ty2, Ty3, and Ty4, which have been shown to specifically integrate upstream to genes that are transcribed by RNA polymerase III (61-63), and for Ty5, which integrates into regions of silent chromatin via yeast proteins Sir (64,65). Like Sir proteins in yeast, the products of Pc-G genes in upper eukaryotes are involved in the maintenance of the silent state of chromatin, possibly by recruitment of histone deacetylase enzymes (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Originally identified as a degenerate element at the ends of Saccharomyces cerevisiae chromosomes (39), the Voytas laboratory recovered an active copy from Saccharomyces paradoxus and transferred it into S. cerevisiae (3). In this context, they showed that Ty5 inserted into heterochromatic DNA (40). Mutations in Sir3p or Sir4p that disrupted silencing of telomeric DNA also resulted in loss of targeting to silenced regions (41).…”
Section: Potential Deleterious Retrovirus Insertions Fueled Investigamentioning
confidence: 99%
“…The ability of these elements to selectively integrate into specific target sequences has been paramount to their success because the employment of specific targeting mechanisms has allowed these retrotransposons to propagate within host genomes without disrupting genes and compromising the host's survival (Levin and Moran 2011). The long terminal repeat (LTR) retrotransposons Ty1, Ty3, and Ty5 of Saccharomyces cerevisiae avoid causing damage to the host by targeting noncoding genomic regions; Ty1 and Ty3 integrate upstream of RNA polemerase III-transcribed genes, while Ty5 integrates into heterochromatin (Chalker and Sandmeyer 1990;1992;Ji et al 1993;Kirchner et al 1995;Devine and Boeke 1996;Zou et al 1996;Zou and Voytas 1997;Yieh et al 2000;Sandmeyer 2003;Lesage and Todeschini 2005).…”
mentioning
confidence: 99%
“…The ability of these elements to selectively integrate into specific target sequences has been paramount to their success because the employment of specific targeting mechanisms has allowed these retrotransposons to propagate within host genomes without disrupting genes and compromising the host's survival (Levin and Moran 2011). The long terminal repeat (LTR) retrotransposons Ty1, Ty3, and Ty5 of Saccharomyces cerevisiae avoid causing damage to the host by targeting noncoding genomic regions; Ty1 and Ty3 integrate upstream of RNA polemerase III-transcribed genes, while Ty5 integrates into heterochromatin (Chalker and Sandmeyer 1990;1992;Ji et al 1993;Kirchner et al 1995;Devine and Boeke 1996;Zou et al 1996;Zou and Voytas 1997;Yieh et al 2000;Sandmeyer 2003;Lesage and Todeschini 2005).In Schizosaccharomyces pombe, the LTR retrotransposon Tf1 has a unique targeting mechanism that directs integration to promoters of RNA polymerase II-transcribed genes with a bias for the promoters of stress-response genes (Behrens et al 2000;Singleton and Levin 2002;Bowen et al 2003;Leem et al 2008;Guo and Levin 2010). Surprisingly, insertion of Tf1 into promoters rarely reduces the expression of their downstream genes, and in approximately 40% of cases, it enhances it (Feng et al 2013).…”
mentioning
confidence: 99%